Substantial enhancement of anaerobic pyridine bio-mineralization by electrical stimulation. (1st March 2018) - Jiang, Xinbai; Shen, Jinyou; Xu, Kaichun; Chen, Dan; Mu, Yang; Sun, Xiuyun; Han, Weiqing; Li, Jiansheng; Wang, Lianjun
Abstract: Due to highly recalcitrant and toxicological nature of pyridine, the conventional anaerobic bioprocess is often limited by low removal rate and poor process stability. In this study, an electricity-assisted anaerobic system was developed in order to enhance biodegradation of pyridine from wastewater. The results showed that the performance and stability of the anaerobic reactor was remarkably improved for pyridine biodegradation with the applied direct current of 0.3 mA, where the efficiencies of pyridine and total organic carbon removal as well as NH4 + -N formation were as high as 100.0%, 96.1 ± 1.2% and 60.1 ± 2.1% respectively. The compact biofilm due to electrical stimulation as well as the microaerobic environment in the bioanode might promote pyridine bio-mineralization in the anaerobic reactor. Moreover, the species related to pyridine biodegradation ( Desulfovibrio, Dokdonella, Hydrogenophaga, and Paracoccus ) were enriched in the anodic biofilm, which would be another reason for better reactor performance. This study demonstrated that electrical stimulation would be a potential alternative for the enhancement of pyridine removal from wastewater in anaerobic systems. Graphical abstract: Highlights: Pyridine degradation was improved in the anaerobic system assisted by electricity. The ability to resist environmental stress was strengthened in the system. Compact biofilm was formed on the electrode due to the electrical stimulation. Partial oxygen produced on the anode benefited pyridine degradation. The species related to pyridine biodegradation appeared enriched in the biofilms.